Preparation and electrochemical corrosion behaviour of 3D large-sized nanocrystalline copper bulk in solutions with chloride ions. (18th August 2019) - Luo, Wei; Zhou, Jian; Xu, Yiming; Lou, Yuan; Hu, Lei; Zhu, Jun; Yan, Mi
ABSTRACT: A 3D large-sized nanocrystalline (NC) copper bulk was prepared by inert gas condensation and in situ warm compress, the density of which was 99.51% of theoretical value. Electrochemical methods and XRD、EDS、SEM technique were used to investigate the anodic polarisation behaviour of NC copper in solutions with chloride ions. NC copper exhibited a different anodic polarisation behaviour from its coarse-grain (CG) counterpart in 0.47 wt-% NaCl solution. No second passivity was observed for NC copper, while there was a notable second passivity for CG copper. Compared with CG copper, the corrosion resistance of NC copper decreased. The anodic polarisation behaviour of NC copper changed significantly when 10 4  ppm Cl − was added in 0.3% Na2 SO4 solution. Attributed to the CuCl protective film on NC copper, the critical current intensity decreased and the decreasing rate of anodic current intensity lowed notably in activity-passivity zone.